Optimal Endometrial Thickness in Fresh and Frozen-Thaw In Vitro Fertilization Cycles: An Analysis of Live Birth Rates From 96, 000 Autologous Embryo Transfers. Issue 8 (August 2022) - Mahutte, Neal; Hartman, Michael; Meng, Lynn; Lanes, Andrea; Luo, Zhong-Cheng; Liu, Kimberly E.
Abstract : (Abstracted from Fertil Steril 2022;117:792–800) A routine procedure of in vitro fertilization (IVF) cycles is to measure the endometrial thickness, as it has been determined that a measurement of <8 mm at human chorionic gonadotropin (HCG) trigger in fresh IVF–embryo transfer (IVF-ET) can increase the risk of ectopic pregnancy, spontaneous abortion, low birth weight, placenta previa, and other obstetric complications. In direct dichotomy to this, an endometrial thickness above 7 to 8 mm has a general association of improved IVF outcomes.